Herbage yield and nitrogen accumulation by seven legume crops on acid and neutral soils in a subarctic environment - Sparrow, Stephen D.; Cochran, Verlan L.; Sparrow, Elena B. (Canadian Journal of Plant Science, 1993)
Alfalfa (Medicago sativa L.), red clover (Trifolium pratense L.), yellow sweet-clover (Medicago officinalis L.), fababean (Vicia faba L.), lentil (Lens culinaris Medik.), pea (Pisum sativum L.), and white lupin (Lupinus albus L.) were evaluated as annual crops in central Alaska on neutral and acid soils for their potential herbage productivity and N accumulation. Herbage dry matter yields were high on the neutral soil, with an overall average yield of 6927 kg ha −1 . Yields were much lower at the cooler, acid soil site with an overall average yield of 3743 kg ha −1 for inoculated legumes. Herbage N concentrations ranged from 14 to 36 mg g −1 . Amounts of N-fixation, as estimated by the total N difference method, ranged from < 50 kgha −1 for some legumes on the acid soil to > 200 kg ha −1 for fababean on the neutral soil. Inoculation resulted in increases in nodulation, growth and apparent N-fixation on the acid soil where legumes had not previously been grown, but were usually not significant on the neutral soil where legumes had been grown for many years. Liming the acid soil resulted in significant increases in soil pH and in nodulation, herbage yield, and herbage N yield. Key words: Forage legume crops, Alaska, liming, N-fixation